(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
In this article based on the manifestation of guilt, causing dissatisfaction among students, offending others without reason, and anxiety factors, the dominance of autoaggression determinants was substantiated as a result of increasing the qualities of fear, regret, remorse, and remorse in the manifestation of characteristics related to personal life and the family environment.